Comparing the effect of group- based training along with text messaging and compact disc- based training on men's knowledge and attitude about participation in perinatal care: a cluster randomized control trial - Vahideh Firouzan; Mahnaz Noroozi; Mojgan Mirghafourvand; Ziba Farajzadegan (BMC, 2020)
Abstract Background Men's participation in perinatal care is one of the key factors in promoting maternal and neonatal health. The effects of various methods of training on men's knowledge and attitude about participation in perinatal care can be different. So, this study aimed to compare the effect of two methods of training on men's knowledge and attitude about participation in perinatal care. Methods This cluster randomized control trial was conducted in three midwifery clinics in Tabriz, Iran between May and August 2018. Each clinic was randomly assigned to intervention (group- based training along with text messaging and CD- based training) and control groups. Seventy-five men were enrolled in three groups and evaluated for their knowledge and attitude about participation in perinatal care. Before and 3 months after the intervention, a researcher-made questionnaire was completed by the participants. Data were analyzed using descriptive and inferential statistics (paired t-test, one-way ANOVA, ANCOVA, chi-square, Kruskal-Wallis and Fisher exact tests). Results The mean (SD) score of men, s knowledge and attitude about participation in perinatal care had a significant increase in group- based training along with text messaging after the intervention compared to the score of before the intervention (p < 0.001, p = 0.005, respectively), but the mean (SD) score of men, s knowledge and attitude had not a significant increase in CD- based training and control group after the intervention compared to the score of before the intervention. The mean (SD) score of men,s knowledge and attitude about participation in perinatal care in group- based training along with text messaging were significantly higher than in CD- based training (p < 0.001, p = 0.039, respectively) and control group (p = 0.001, p = 0.021, respectively) after the intervention, respectively. However, the mean (SD) score of men, s knowledge and attitude in CD- based training were not significantly different from the control group after the intervention. Conclusion Group- based training along with text messaging was more effective in improving the knowledge and attitude of men about participation in perinatal care compared to CD- based training. So, its implication in educational programs for the men is recommended. Trial registration IRCT, IRCT20160224026756N4 . Registered 27 May 2018.